Consumer Subjective Values and their Reflection on Fashion Design: وسن خليل إبراهيم (Al-Academy, 2019)
This paper deals with the subjective reflections of consumer values ​​on fashion design. The consumer self is determined by the consumer's idea of ​​himself, according to the intellectual, spiritual and social values, and these values ​​take their intellectual reflection in the form of material values ​​that the consumer finds in fashion design. These values ​​are based on considerations between what is intellectual represented by the values ​​of the consumer, and what is material determined by the fashion design, which also proceed from values that are visible or implied in costume design, such as the function, beauty and symbol. The consumer self gets its material image represented in the fashion design when the macroscopic apparent values represent one or more of the values of the consumer